Comparison of the restriction enzyme profiles of herpesvirus isolates from captive wildlife - Allaudin, Zeenathul Nazariah; A. P., Zanariah; Mohd Lila, Mohd Azmi (Veterinary Association Malaysia, 2010)
Herpesvirus has been commonly isolated from captive wildlife in animal sanctuaries. Other then identification of the virus, attempts to trace the origin of the virus were initiated based on DNA restriction enzymes (RE) analysis. Two isolates from gaurs (UPMV4/05, UPMV5/05) and an isolate from a Malayan sun bear (UPMV19/05) were examined for a homologous relationship among them. As expected, the DNA from UPMV4/05 and UPMV5/05 showed close RE similarity in comparison to UPMV19/05. The RE patterns from this herpesvirus isolates indicate a possible evolution from the same origin, bovine herpes virus (BHV). The present study showed the DNA of isolates UPMV4/05, UPMV5/05 and UPM19/05 to have an average molecular weight 0f 112x10⁶ Dalton.